Intravenous omega-3 fatty acids are associated with better clinical outcome and less inflammation in patients with predicted severe acute pancreatitis: A randomised double blind controlled trial. Issue 9 (September 2020) - Al-Leswas, D.; Eltweri, A.M.; Chung, W.-Y.; Arshad, A.; Stephenson, J.A.; Al-Taan, O.; Pollard, C.; Fisk, H.L.; Calder, P.C.; Garcea, G.; Metcalfe, M.S.; Dennison, A.R.
Summary: Background and aims: Omega-3 fatty acids (FA) can ameliorate the hyper-inflammatory response that occurs in conditions such as severe acute pancreatitis (SAP) and this may improve clinical outcome. We tested the hypothesis that parenteral omega-3 FA from a lipid emulsion that includes fish oil could be beneficial in patients with predicted SAP by reducing C-reactive protein (CRP) concentration (primary outcome), and modulating the inflammatory response and improving clinical outcome (secondary outcomes). Methods: In a phase II randomized double-blind single-centre controlled trial, patients with predicted SAP were randomised to receive a daily infusion of fish oil containing lipid emulsion (Lipidem® 20%, BBraun) for 7 days (n = 23) or a daily infusion of a lipid emulsion without fish oil (Lipofundin® MCT 20%, BBraun) (n = 22). Results: On admission, both groups had comparable pancreatitis predicted severity and APACHE II scores. Administration of fish oil resulted in lower total blood leukocyte number (P = 0.04), CRP (P = 0.013), interleukin-8 (P = 0.05) and intercellular adhesion molecule 1 (P = 0.01) concentrations, multiple organ dysfunction score, sequential organ failure assessment score (P = 0.004), early warning score (P = 0.01), and systemic inflammatory response syndrome (P = 0.03) compared to the control group. The fish oil group had fewer new organ failures (P = 0.07), lower critical care admission rate (P = 0.06), shorter critical care stay (P = 0.03) and shorter total hospital stay (P = 0.04). Conclusions: It is concluded that intravenous administration of a fish oil containing lipid emulsion, a source of omega-3 FA, improves clinical outcomes in patients with predicted SAP, benefits that may be linked to reduced inflammation. ClinicalTrials.gov number: NCT01745861 . EU Clinical Trials Register: EudraCT (2010-018660-16).